Gambaran Sikap Caring Mahasiswa Keperawatan ‎ Yang Telah Menjalani ‎ Praktik Klinik Di Rumah Sakit - novita setyowati; Elfi Quyumi Rahmawati (coba, 2018)
Nursing is described as a profession that works lovingly and caring. Establishing a caring attitude is not easy, it needs support and reinforcement during lectures. Caring behavior has not been applied optimally in health services. The purpose of this study is to know the description of caring attitude of nursing students during clinical practice in hospital. Ten student participants were observed and interviewed in depth. Data were analyzed thematically. The study found five themes: humanistic, trust, confidence, helping the patient's basic needs. Caring is the center and focus that unites a professional nurse. Characteristics of caring is essential to meeting basic human needs (Thomas et al., 2005). Technical ability requires sufficient field experience to train students psychomotor. This study recommends the need to cultivate caring attitude through continuous education, supervision, and intensive briefing. Key word : attitude, caring, nursing